A gestão dos riscos globais das mudanças climáticas pelo estado de direito ambiental - Sampaio, Anelice de (Universidade do Vale do Rio dos Sinos, 2012)
This work aims at description, research and analysis of the management of global risks caused by climate change according to the State of Environmental Law. Society, contemporary as global risks producer, causes the entire society to rethink the way how to live. Specifically, requiring a new approach of social systems, particularly the legal system and political system. Thus, we adopt the theory of autopoietic social systems of Niklas Luhmann and the theory of risk society of Ulrich Beck, and these were the only ones capable of giving the theoretical framework necessary for the development of this research. The risks from the environment cause irritations in social systems, which produce resonances in both systems themselves as in other social systems. Environmental law is therefore a response to the (auto) irritation produced in the legal system. The classical law no longer has the capacity to provide adequate answers that this society needs. Thus, it is necessary a new theory of law, which it is ready to make decisions that anticipate the occurrence of environmental damages, future-oriented, avoiding or mitigating risks, and especially climate change. In this context, a new State model arises; which falls among fundamental rights the right to an ecologically balanced environment. For both the present and for future generations, that assures to lead society in a more sustainable modus vivendi. However, not only States have the duty to protect the environment, but the whole society, ensuring that there are life conditions for every human inhabitant of this planet called Earth.
Keywords: Gestão; Mudanças climáticas; Direito; Política; Estado; Management; Climate change; Law; Politics; State; ACCNPQ::Ciências Sociais Aplicadas::Direito